1996
DOI: 10.1111/j.1530-0277.1996.tb01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Short‐Term Survival in Alcoholic Hepatitis in Japan: Analysis by Logistic Regression

Abstract: Prognostic factors for the outcome of patients with alcoholic hepatitis were identified by logistic regression analysis. To predict the outcome immediately after admission, clinical data from 97 patients with alcoholic hepatitis on admission were introduced to multivariate analysis. Independent prognostic factors for favorable outcome were hepaplastin time, peripheral white blood cell count, age (40 to 60 years), and serum creatinine level (below 1.4 mg/dl). Sensitivity, specificity, positive predictive value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…In the present population-based study from a large Canadian metropolitan centre, we describe prognostic factors and the predictive utility of well-known risk scores in patients hospitalized for AH. As expected, older age and indicators of greater hepatic and renal dysfunction were associated with 90-day mortality (9,31). In univariate analysis, patients who died had higher MELD and Maddrey DF scores, and greater INR and serum creatinine concentrations, supporting the prognostic significance of these factors.…”
Section: Discussionsupporting
confidence: 63%
“…In the present population-based study from a large Canadian metropolitan centre, we describe prognostic factors and the predictive utility of well-known risk scores in patients hospitalized for AH. As expected, older age and indicators of greater hepatic and renal dysfunction were associated with 90-day mortality (9,31). In univariate analysis, patients who died had higher MELD and Maddrey DF scores, and greater INR and serum creatinine concentrations, supporting the prognostic significance of these factors.…”
Section: Discussionsupporting
confidence: 63%
“…The association between mortality and bilirubin, creatinine and encephalopathy has been previously reported 22,23 . In a multivariate analysis, our results confirmed that encephalopathy, bilirubin and creatinine were independently associated with 3‐month mortality.…”
Section: Discussionsupporting
confidence: 89%
“…The risk of mortality in this case was 98% on admission, according to the formula reported by Kumashiro et al (1996), and we believed that his prognosis was very poor. The formula for the predictive prognosis of SAH is as follows:…”
Section: Laboratory Datasupporting
confidence: 50%
“…The standard treatment methods include prednisolone (PSL) and nutritional support; however, the survival rate in Japan is approximately 20%, suggesting that we do not yet have an established treatment modality for this disease. Here we report a case of SAH in which a high risk to mortality was suggested by multivariate analysis (Kumashiro et al, 1996). We applied a new treatment with granulocyte and monocyte adsorption apheresis (GCAP) using an Adacolumn (JIMRO, Takasaki, Japan).…”
mentioning
confidence: 99%